Desarrollo de una herramienta educativa para la ejecución de incisiones quirúrgicas y la mejora del pulso a la hora de realizarlas (2017)
The infection and the dissatisfaction of the people after a surgical procedure is mainly due to the elaboration of bad performed surgical incisions. This graduation proyect evalues the functioning of a tool elaborated from virtual reality and the haptic element Phantom Omni which aims to help the enhancement of the fine motor specifically the enhancement in the elaboration of straight lines that helps future surgeons to make better incisions. The point of comparison of the tool is with one of the methods the doctors use for that purpose, drawing lines on papers. The data analysis is performed with image processing. Calibration tests were performed which let us know in which moment an acceptable result was obtained, those were used for the final test which first realize the test in sheets, then tests in the tool with the Phantom, and finally in sheets again. The obtained results show that, indeed, the elaboration...